The Impact of Avoidant/Disengagement Coping and Social Support on the Mental Health of Adolescent Victims of Sexual Violence in Eastern Congo - Verelst, An; Bal, Sarah; De Schryver, Maarten; Say Kana, Nanc; Broekaert, Eric; Derluyn, Ilse (Frontiers in Psychiatry, 2020)
Introduction Eastern Congo has been affected by armed conflict for decades while the rampant use of sexual violence has left many women and girls dealing with a wide range of consequences of sexual violence. For adolescent victims the psychosocial impact of sexual violence is devastating. However, the role of avoidant/disengagement coping and family support on the mental health impact of sexual violence remains unclear. Methods The study design was a cross-sectional, population-based survey in which 1,305 school-going adolescent girls aged 11 to 23 participated. Mental health symptoms (IES-R and HSCL-37A), family support (MSPSS), avoidant/disengagement (Kidcope), war-related traumatic events (ACEES), experiences of sexual violence, daily stressors, and stigmatization (ACEDSS) were administered through self-report measures. Hierarchical multiple regression analysis was carried out with mental health outcomes as dependent variables for different types of sexual violence. Finally, several ANCOVA models were defined to explore possible interaction effects of avoidant/disengagement coping and family support with stigmatization, daily stressors and war-related traumatic exposure. Results For girls who did not report sexual violence, avoidant/disengagement coping has a direct negative effect on all psychological symptoms. For victims of sexual violence, when high levels of stigma were reported, avoidant/disengagement coping possibly served as a protective factor, as shown by the interaction effect between avoidance/disengagement coping and stigmatization on mental health outcomes. In victims of sexual violence however, high levels of daily stressors combined with avoidant/disengagement strategies showed a strong increase in posttraumatic stress symptoms. Interestingly, the mental health impact of sexual violence was not mitigated by support by family members. For girls who reported a nonconsensual sexual experience without labelling it as rape and at the same time testified to have a lot of family support, there was a positive association between stressors (daily stressors, stigma, and war-related trauma) and posttraumatic stress symptoms. Conclusions These results of this study underwrite to the importance of looking beyond the straightforward negative impact of avoidant/disengagement coping strategies on mental health in adolescent victims of sexual violence. While avoidant/disengagement coping can have a negative impact on psychosocial well-being on adolescent victims of sexual violence, in case of high levels of stigmatization it can as well protect them from posttraumatic stress or anxiety. Furthermore these findings speak to the importance of exploring the diversified relationship between risk and protective factors, such as avoidant/disengagement coping strategies and family support, that shape the mental health impact of sexual violence in adolescent victims.